Duodenal ulcer: a review of recent literature and a comparison of the results of medical and surgical treatment in a series of 480 cases - Farquharson, E. Leslie (The University of Edinburgh, 1932)
In the more recent publications dealing with any branch of the wide subject, comprised under the heading of "Peptic Ulcer ", the authors have in many cases prefaced their remarks with an apology for adding to the already over -burdened literature. If, in offering a thesis on "Duodenal Ulcer ", the writer feels that he is exempt from the necessity of making such an apology, it is not because he can claim to have added anything to our knowledge of the subject, but rather from the very opposite reason. In this thesis is to be found little that is new, and perhaps even less that is original. But in a subject so controversial as this, where there is already in the literature a super- abundance of original investigations and original conclusions, it perhaps serves a more useful purpose to collect and comment upon the opinions of others, and by so doing, to attempt a general survey of the more controversial aspects of this disease, in the light of recent research.

In general, this thesis has been confined to the discussion of Duodenal Ulcer alone. In the sections on Aetiology and Pathogenesis, however, it has been found impossible to differentiate between Gastric and Duodenal Ulcer, and here the two conditions have been considered together.

It is becoming more generally recognised that the whole question of ulcer pathogenesis, is closely related to the existence of abnormal physiological conditions in the stomach. When a discussion of this "morbid physiology" was attempted, it became at once apparent that there was no uniformity of opinion regarding the normal physiology of gastric digestion, and a further chapter has been included to discuss the more recent views on this subject.

With regard to the investigation carried out by the writer into the after histories of duodenal ulcer patients, a brief word of explanation and apology is due. A follow up study of i!edical and Surgical results in this condition is by no means a new venture, but as far as can be ascertained, it has not been done before in Edinburgh.

It has been pointed out that adjudication between Medicine and Surgery cannot fairly be made on a direct comparison of the results of treatment in each case, as many of the cases operated on have been specially selected for surgery, and their inclusion in the surgical series confers an unfair advantage. The writer has attempted to make the comparison in a series of cases where this criticism cannot be applied. By excluding from the surgical series cases which may be said to have been specially selected for operation, the investigation has been confined to that type of ulcer which presents the greatest problem in treatment,- the chronic ulcer without stenosis.